Cognitive semantics and schemas-image in the phytononym system of the jacaru-speakers - Escobar Zapata, Emérita (2015)
Our main purpouse is to interpret unpublished lexical data about botanic species from Tupe and Aiza (Yauyos, Lima), where the jacaru language is spoken today. After contrasting this written sources in fieldwork, we analyze them from a cognitive viewpoint as image schemas.